Muscular adaptations in low- versus high-load resistance training: A meta-analysis - Schoenfeld, Brad J.; Wilson, Jacob M.; Lowery, Ryan P.; Krieger, James W. (European journal of sport science, 2016)
There has been much debate as to optimal loading strategies for maximising the adaptive response to resistance exercise. The purpose of this paper therefore was to conduct a meta-analysis of randomised controlled trials to compare the effects of low-load (≤60% 1 repetition maximum [RM]) versus high-load (≥65% 1 RM) training in enhancing post-exercise muscular adaptations. The strength analysis comprised 251 subjects and 32 effect sizes (ESs), nested within 20 treatment groups and 9 studies. The hypertrophy analysis comprised 191 subjects and 34 ESs, nested with 17 treatment groups and 8 studies. There was a trend for strength outcomes to be greater with high loads compared to low loads (difference = 1.07 ± 0.60; CI: −0.18, 2.32; p = 0.09). The mean ES for low loads was 1.23 ± 0.43 (CI: 0.32, 2.13). The mean ES for high loads was 2.30 ± 0.43 (CI: 1.41, 3.19). There was a trend for hypertrophy outcomes to be greater with high loads compared to low loads (difference = 0.43 ± 0.24; CI: −0.05, 0.92; p = 0.076). The mean ES for low loads was 0.39 ± 0.17 (CI: 0.05, 0.73). The mean ES for high loads was 0.82 ± 0.17 (CI: 0.49, 1.16). In conclusion, training with loads ≤50% 1 RM was found to promote substantial increases in muscle strength and hypertrophy in untrained individuals, but a trend was noted for superiority of heavy loading with respect to these outcome measures with null findings likely attributed to a relatively small number of studies on the topic.